Radiative MHD Flow of Third-Grade Fluid Towards a Stretched Cylinder - Shafiq, Anum; Hammouch, Z.; Öztop, Hakan Fehmi (Springer International Publishing Ag, 2020)
This work is concerned with magnetohydrodynamic (MHD) stagnation point flow of third-grade fluid due to a stretching cylinder. Thermal radiation effects are considered in the analysis of heat transfer phenomenon. Joule heating and viscous dissipation effects are also retained. The resulting nonlinear system is computed for the series solutions. Influence of various physical parameters on the velocity and temperature profiles are scrutinized graphically. Comparison between Newtonian and third-grade fluids is made. Velocity and temperature profiles in the presence/absence of stagnation point are discussed graphically. Numerical values of skin friction and Nusselt number are also computed and interpreted. The comparison is conducted between Newtonian and third-grade fluids velocities in the presence of magnetohydrodynamic over a flat plat for two cases (i) without stagnation point (ii) with stagnation point. It is observed that in the presence of MHD, the velocity profile is higher for third-grade fluid for both the cases. On the other hand it is also examined that the velocity profile is higher for both Newtonian and third-grade fluids with stagnation point.
4th International Conference on Computational Mathematics and Engineering Sciences (CMES) -- APR 20-22, 2019 -- Akdeniz Univ, Antalya, TURKEY
Keywords: Viscous dissipation; Stagnation point; Thermal radiation; Magnetohydrodynamics (MHD); Third-grade fluid; Stretching cylinder